Musikerne, bransjen og samfunnet - Røyseng, Sigrid; Stavrum, Heidi; Vinge, John (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Among all artists in Norway, musicians are the majority, and this book is all about them. Musicians work in many different fields, across a broad spectrum of professional roles, and they express themselves in many different genres. You experience them at clubs and on concert stages nationally and internationally. You find them at the podium leading a philharmonic and in the orchestra pit when musicals, plays, dance, and opera are on the program. You encounter them as teachers in music schools, elementary schools, and high schools. You meet them as musical directors and motivators behind choirs, marching bands, and folk music groups. You meet them in our churches and as driving forces in big cities and remote towns, in school gymnasiums and community house auditoriums. The twelve chapters focus attention on musicians' actual jobs and daily work life. The book describes transformations and trends within the music industry and society in general that have an impact on musicians' professional development and wellbeing. The book's four parts look at changes in the musician's role, professionalization, digitalization, and cultural-political and societal developments that all influence working conditions in the music industry, resulting in differing circumstances for different types of musicians.